Off‐target effects of oral anticoagulants – vascular effects of vitamin K antagonist and non‐vitamin K antagonist oral anticoagulant dabigatran etexilate. (28th March 2021) - van Gorp, Rick H.; Dijkgraaf, Ingrid; Bröker, Vanessa; Bauwens, Matthias; Leenders, Peter; Jennen, Danyel; Dweck, Marc R.; Bucerius, Jan; Briedé, Jacco J.; van Ryn, Joanne; Brandenburg, Vincent; Mottaghy, Felix; et al.
Abstract: Introduction: Vitamin K antagonists (VKA) and non‐vitamin K oral antagonist anticoagulants (NOAC) are used in the clinic to reduce risk of thrombosis. However, they also exhibit vascular off‐target effects. The aim of this study is to compare VKA and NOAC on atherosclerosis progression and calcification in an experimental setup. Material and methods: Female Apoe −/− mice (age 12 weeks) were fed Western‐type diet as control or supplemented with dabigatran etexilate or warfarin for 6 or 18 weeks. Vascular calcification was measured in whole aortic arches using µCT and [ 18 F]‐NaF. Atherosclerotic burden was assessed by (immuno)histochemistry. Additionally, in vitro effects of warfarin, thrombin, and dabigatran on primary vascular smooth muscle cells (VSMC) were assessed. Results: Short‐term treatment with warfarin promoted formation of atherosclerotic lesions with a pro‐inflammatory phenotype, and more rapid plaque progression compared with control and dabigatran. In contrast, dabigatran significantly reduced plaque progression compared with control. Long‐term warfarin treatment significantly increased both presence and activity of plaque calcification compared with control and dabigatran. Calcification induced by warfarin treatment was accompanied by increased presence of uncarboxylated matrix Gla protein. In vitro, both warfarin and thrombin significantly increased VSMC oxidative stress and extracellular vesicle release, which was prevented by dabigatran. Conclusion: Warfarin aggravates atherosclerotic disease activity, increasing plaque inflammation, active calcification, and plaque progression. Dabigatran lacks undesired vascular side effects and reveals beneficial effects on atherosclerosis progression and calcification. The choice of anticoagulation impacts atherosclerotic disease by differential off target effect. Future clinical studies should test whether this beneficial effect also applies to patients.